Auto Immune Hemolytic Anemia (AIHA) Patients Profile and Treatment Response to Corticosteroids in Cipto Mangunkusumo Hospital - Wulyo Rajabto; Djumhana Atmakusuma; Siti Setiati (Jurnal Penyakit Dalam Indonesia)
Introduction. Autoimmune hemolytic anemia (AIHA) is one of the immunological diseases that causes hemolysis. Data on demographic characteristics and treatment response of AIHA patients has not available in Indonesia. This study was conducted to identify the profile of autoimmune hemolytic anemia (AIHA) patients and their response of treatment after receiving corticosteroid treatment.